A Pilot Study for Testing the Effectiveness and Cost-Efficiency of Lottery Incentive in mHealth App that Promotes Walking. (May 2022) - Lee, Changseok; Chung, Kyong-Mee
This is a pilot study that investigated differences in effectiveness, maintenance of effectiveness, cost-efficiency, satisfaction, and usability of a lottery incentive via mobile devices to promote walking, depending on the chance of winning the lottery, the amount of the prize, and gender. Sixty-six college students (male = 26) were randomly assigned to 3 groups: 10% chance of a big prize (10% + B), 50% chance of a medium prize (50% + M), and 100% chance of a small prize (100% + S). Step counts were collected through mobile devices before and after the intervention, as well as at the 2-month follow-up. The results showed significant increases in the step counts among males after the intervention in the 10% + B and the 50% + M groups, and females in the 100% + S group. Only males in the 50% + M group exhibited maintenance in effectiveness during follow-up. With regard to cost-efficiency, the 10% + B and the 50% + M male groups, which showed significant differences in effectiveness, were compared, and no significant difference was found. With regard to intervention satisfaction, satisfaction of the 10% + B group was lower than that of the 100% + S group. There were no significant interactions or main effects regarding the usability of the intervention. The results suggest that a lottery incentive is effective only for men to promote walking when a medium size prize is given with a 50% of chance of winning the lottery.